Prevention of occupational laryngitis in teachers - Savushina, I. V.; Pavlenko, O. I.; Zos’ka, Y. V. (Medicni Perspektivi, 2020)
The number of people in need of phoniatric help is constantly increasing. People with voice problems are of working age. The object of researche: lowering risk of progression of vocal pathology based on a comprehensive system of management of teachers’ occupational risks. Hygienic, epidemiological, sanitary-statistical, in-depth medical examination method and mathematical-statistical methods were applied. Working conditions of teachers are characterized by complex effects of harmful production factors, which can reach 3d degree of 3d class of harmful work by intensity (according to the calculated points 3,63), 2nd degree of 3d class of harmful pressure on vocal apparatus (27,52±3,54 hours), 1st degree of 3d class of harmful by equivalent noise level and unfavorable microclimate. The most widespread pathologies of the vocal apparatus are chronic hypertrophic laryngitis (190,20±22,61) and chronic catarrhal laryngitis (131,00±15,07 cases). Almost 70% of occupational laryngitis cases are in the age group of 46-60 years. The critical length of service influenced by voice load is 10-19 years. The length of service more than 20 years in conditions of voice load increases the etiological percent of occupational pathology causes to 81,8%. Therefore, an age of 45,8±0,5 and older is dangerous for the occupational laryngitis progression and requires a special approach of development and implementation of preventive measures aimed at maintaining of occupational health. Suggested complex of measures increase the healthy life by 7,3 years and reduce the loss of healthy life years determined by the impact of voice activity by 7,1 years. At the same time for physical health component (PH) by 4,5 and 4,3, and the psychological health component (MH) by 10,3 and 10,1 years QALY respectively.